Strengthening Urban Identity Through Semanggi: A Local Wisdom-Based City Branding Strategy for Surabaya - Bawa Mulyono Hadi; Sugiharto Sugiharto; Tonny Hendartono; Ristanti Ristanti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
City branding is a strategic approach to enhancing a city's competitiveness by leveraging unique local characteristics to create a strong and distinctive identity. This study examines the role of semanggi—a traditional Surabaya dish—as a cultural icon in strengthening the city's branding. Although semanggi carries deep symbolic meaning and historical significance for Surabaya’s residents, its potential as a city branding asset remains underutilized in formal tourism and marketing programs. Adopting a qualitative exploratory case study design, data were collected through in-depth interviews, participant observation, and document analysis involving local stakeholders, small and medium-sized culinary enterprises, cultural figures, and municipal representatives. Thematic analysis identified five key dimensions of semanggi’s role in city branding: (1) visual representation in urban spaces and promotional media; (2) cultural narratives and heritage preservation; (3) community pride and participation; (4) local economic resilience; and (5) strategic promotion by municipal authorities. The findings suggest that integrating semanggi into Surabaya’s branding strategy can reinforce cultural identity, differentiate the city in competitive tourism markets, and promote sustainable local entrepreneurship. The study contributes to the theoretical discourse on culinary-based place branding and offers practical recommendations for incorporating local wisdom into destination marketing. Limitations include the single-case scope and qualitative focus, pointing to opportunities for comparative and mixed-method research in the future.